Parameters of physical and chemical quality of the central axis, mesocarp and jackfruit seed submitted to diferente drying processes (Research, Society and Development, 2022)
The drying process aims to reduce the water content, contributing to the conservation, storage and prolonging the shelf life of the food. Different drying methods influence the yield and the quality of the product. Thus, the objective was to observe the influence of drying in an oven and microwave oven on the physical and chemical properties of jackfruit residues. The raw materials were reused from the jackfruits purchased at the Bujari site, Cuité, PB. Central axis, mesocarp and seed were dried at 60 ° C for 300, 360 and 300 min, respectively. The heating ramp in a microwave oven was 3 cycles of 5 min, 100% power and 40 g of sample. The two drying methods caused the concentration of the mineral residue content, total soluble solids and proteins. However, there was a reduction in water content, water activity and pH, increasing the stability of the flours and, consequently, the shelf life. When drying in a microwave oven, the protein concentration was 2.14, 5.33 and 1.45 times for the central axis, mesocarp and seed, respectively, in relation to the in natura residues. The elaborated flours can be considered sources of different minerals. Drying in a microwave oven was considered more efficient in reducing the water content, drying time and quality of the dehydrated product. The use of jackfruit residues and the transformation into value-added flours is important for sustainability and the environment, as it reduces food losses, waste and environmental impact.